Experiences of perioperative staff on the role and behaviour of circulating nurses in the operating room, of private healthcare facilities in the Western Cape - Botha, Andrea Elizabeth (Stellenbosch : Stellenbosch University, 2023)
Thesis (MNur)--Stellenbosch University, 2023.